Abdominal surgery as a possible cause of gastric diverticula: Single center one year experience - Sahin, Abdurrahman; Ozercan, Mubin; Demirel, Ulvi; Yalniz, Mehmet; Bahçecioğlu, İbrahim Halil (My University, 2019)
-
Keywords: Genel ve Dahili Tıp; Cerrahi